L-type association between magnesium intake and human papillomavirus infection in US adult women: based on NHANES 2003–2016 data - Chen, Haiwei; Chen, Xiaotong; Chen, Yuling; Tang, Lixin; Shi, Wen-Jing; Ou, Yu-Hua (Frontiers in Nutrition, 2025)
BackgroundIn the post-vaccine era, adjusting living habits and diet structure has become a new way to prevent Human papillomavirus(HPV). Although dietary factors have received much attention, the association of dietary magnesium with HPV infection remains understudied.MethodUsing NHANES cross-sectional data from 2003 to 2016, this study analyzed the relationship between magnesium intake and HPV infection in 7,246 women aged 18–59 years. Weighted logistic regression and subgroup analysis assessed independent links, while curve fitting and threshold analysis defined dose response and saturation.ResultA significant negative correlation was observed between magnesium intake and the risk of HPV infection. After comprehensive adjustment for potential confounding factors, individuals in the highest quartile of magnesium intake exhibited a statistically significant 29.7% reduction in the risk of HPV infection for each additional unit, compared to those in the lowest quartile (CI:0.554–0.894, p = 0.005). Besides, using smooth curve fitting and threshold analysis, we found an L-shaped dose response between magnesium intake and HPV risk. Below 401 mg/day of magnesium, increased intake is inversely correlated with HPV infection risk. Above this threshold, further increases plateaued in risk reduction.ConclusionModerate magnesium intake has a protective effect against HPV infection. Rationally increasing magnesium intake through dietary channels is expected to serve as an effective preventive measure against HPV infection.